Küre Dağları Milli Parkı Su Kaynaklarının Rekreasyonel Amaçlı Kullanımı - Belkayalı, Nur; Aydın, Miraç (Turkish Science and Technology Publishing (TURSTEP), 2016)
Water is a basic need in order to survive all living beings. The functional use of water through the ages of living space formatted directed, has a significant influence on environmental design. In addition to the use of water for various purposes has refreshing climatic features, to create a living suitable environment for all living things and has the visual aesthetics features, to become an indispensable element in the landscape has provided. Despite the abundance of recreational activities, humans are mostly enjoyed water-based recreational activities. Water-based recreation is no doubt that the increase of needs. Naturally, the water surface provides great advantages in terms of recreation. Water in recreational areas, both inland and coastal water-based activities is an important element. For example, streams, lakes, ponds and dams’ coast, walking, cycling, water sports, picnics, etc. for recreational activities are indispensable elements of life. Core zone and buffer zone of Kure Mountains National Park is a rich area in underground and surface water resources. Canyons, waterfalls, sinkholes and water resources increase the recreational use potential of the area and these unique natural resources in national park make a difference compared to other areas. In this study, recreation potential of water resources in the Kure Mountains National Park was determined in accordance with suitability assessment, in this context national park was evaluated according to the land capability classes, view, vegetation, slope, current land use, recreational infrastructure, water resources, topography and the proximity to the road factors and suitability map was produced. Suggestions for active and passive recreational activities can be done in the appropriate spaces for recreation have been developed.
Keywords: 13. Climate action; 11. Sustainability; 14. Life underwater; 15. Life on land; 6. Clean water